(untitled) (Journal of the College of Basic Education, 2022)
The scenic image of Eid al-Ghadeer achieved wide recognition. Because what the epic is based on is the narration of past events interspersed with dialogue characters, it added vitality to the stage of the poem, and conveyed to the recipient scenes that were distinguished by movement, drawing the state of the characters, and the way of thinking of the character that was reflected in her actions, as well as the dialogue that had a role in defining the dimensions of the event, Adding an element of dynamism to the text.